Curriculum and learning designers’ epistemological views of learning and how they inform design work in universities - Lodge, Jason (Journal of University Teaching and Learning Practice, 2023)
Universities globally have been increasingly looking to bring in professionals with expertise in learning and curriculum design to help with educational innovation. The aim of this study was to explore the epistemological views of learning that people in curriculum and learning design roles use to inform their practice. In this study, ten learning and curriculum designers were interviewed in depth. The participants demonstrated wide and deep knowledge of learning and teaching, drawing on both established notions of constructivism but also on emerging theories and evidence. Combined with extensive experience, the interviews revealed that these learning designers demonstrate high levels of epistemic fluency, adapting and using processes and practices in a dynamic way as task requirements demand. The findings make a contribution to the limited understanding of the knowledge base that curriculum learning designers draw on to carry out their work. The implications of these findings for universities are also discussed.